EP163/#1029 Expression of human leucocyte antigen G (HLA-G) is associated with deep myometrial invasion and worse survival in endometrial carcinoma. (4th December 2022) - Boujelbene, Nadia; Yahia, Hamza Ben; Zemni, Ines; Babay, Wafa; Dhouioui, Sabrine; Ayadi, Mohamed Ali; Ouzari, Hadda-Imene; Mrad, Karima; Yahyaoui, Safia; Zidi, Ines
Abstract : Objectives: Human leukocyte antigen G (HLA-G) is a non-classical class I molecule that regulates many immune functions. This molecule has been proposed to be involved in tumor escape mechanisms. We aimed to investigate immunohistochemical expression of HLA-G molecules in endometrial carcinoma (EC) and its association with myometrial invasion and overall survival rate. Methods: Immunohistochemical analysis using the 4H84 anti-HLA-G monoclonal antibody was performed on a total of 31 patients with EC. Tumor cells that exhibited granular cytoplasmic brown staining were considered to be positive. The association between HLA-G status and myometrial invasion was analyzed using Chi-square test. The survival analysis was evaluated by Kaplan-Meier method. Results: Immunohistochemical analysis of EC revealed HLA-G protein immunoreactivity in 38.7% (12/31) of specimens. We identify 58% (18/13) of patients with more than 50% myometrial invasion. Statistically significant association was found between HLA-G expression and depth of myometrial invasion (p=0, 02). Patients with HLA-G positive tumors had a shorter survival time than those patients with tumors that were HLA-G negative (mean survival = 48 and 84 months, respectively) with significance trend (log-rank p=0.09). Conclusions: Our preliminary data suggest that HLA-G expression in EC may be potentially predictive of extrauterine metastases which are more observed in patients with more than 50% myometrial invasion. Likewise, this expression should be considered as prognostic indicator. This parameter should be evaluated to ensure better management of these patients.